Bound by blood - Ashley, Amanda (Ashley, Amanda. Bound novels., 2011)
The owner of the hottest casino in Nevada, Zack Ravenscroft, who can have any woman that he wants, is drawn to mysterious newcomer Kaitlyn Sherrad, the daughter of the Carpathian Coven's master who is searching for a prince.